2012
DOI: 10.1097/pgp.0b013e31824d354f
|View full text |Cite
|
Sign up to set email alerts
|

Collision Tumor of the Ovary

Abstract: We report the first case of a combined adult granulosa cell tumor and endometrioid carcinoma collision tumor occurring in an ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…A review of the literature identified 19 cases of ovarian epithelial neoplasms, ranging from benign to malignant, that were combined with an AGCT 12–30 . Of the 20 reported cases (including our case), 13 presented with a grossly evident nodule or mass-like area of granulosa cell proliferation, while 7 cases did not display a visible granulosa cell mass (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…A review of the literature identified 19 cases of ovarian epithelial neoplasms, ranging from benign to malignant, that were combined with an AGCT 12–30 . Of the 20 reported cases (including our case), 13 presented with a grossly evident nodule or mass-like area of granulosa cell proliferation, while 7 cases did not display a visible granulosa cell mass (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…9 The histological findings were described for all 45 ovarian collision tumors, with 14 combinations of teratomas and cystadenomas, 9 teratomas and cystadenocarcinomas, 12 cystadenomas/ cystadenocarcinomas and other tumors, 6 teratomas and other tumors, and 4 other extremely rare combinations. 4,[10][11][12] Diagnostic imaging was shown for 25 tumors, including 17 MRI, 3 CT, and 5 ultrasonography scans. 2,5,6,13 The rare imaging reports of ovarian collision tumors may reflect insufficient recognition of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been 25 reports on 45 ovarian collision tumors in English language literature, 1–6,9–25 since YM Bhende reported a Brenner tumor in the wall of a serous cystadenoma in 1947 9 . The histological findings were described for all 45 ovarian collision tumors, with 14 combinations of teratomas and cystadenomas, 9 teratomas and cystadenocarcinomas, 12 cystadenomas/cystadenocarcinomas and other tumors, 6 teratomas and other tumors, and 4 other extremely rare combinations 4,10–12 . Diagnostic imaging was shown for 25 tumors, including 17 MRI, 3 CT, and 5 ultrasonography scans 2,5,6,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Para reducir el riesgo de diagnóstico erróneo es importante el trabajo interdisciplinario -entre médicos oncólogos, médico cirujanos y médicos patólogos-del tumor de colisión uterino (9,10), ya que puede tener implicaciones en el tratamiento y en el pronóstico. Presentamos un caso de tumor de colisión de útero conformado por un adenocarcinoma endometrial de tipo seroso papilar, de alto grado, y un adenosarcoma de cérvix con elementos heterólogos rabdomioblásticos, con el objetivo de realizar una revisión de la literatura respecto al diagnóstico histopatológico, tratamiento y pronóstico de esta condición.…”
Section: Introductionunclassified